Cyanobacteria and Chloroflexota cooperate to structure light-responsive biofilms - Freddy Bunbury; Carlos Rivas; Victoria Calatrava; Andrey V. Malkovskiy; Lydia-Marie Joubert; Amar D. Parvate; James E. Evans; Arthur R. Grossman; Devaki Bhaya (Proceedings of the National Academy of Sciences, 2025)
Microbial mats are stratified communities often dominated by unicellular and filamentous phototrophs within an exopolymer matrix. It is challenging to quantify the dynamic responses of community members in situ as they experience steep gradients and rapid fluctuations of light. To address this, we developed a binary consortium using two representative isolates from hot spring mats: the unicellular oxygenic phototrophic cyanobacterium Synechococcus OS-B′ (Syn OS-B′) and the filamentous anoxygenic phototroph Chloroflexus MS-CIW-1 (Chfl MS-1). We quantified the motility of individual cells and entire colonies and demonstrated that Chfl MS-1 formed bundles of filaments that moved in all directions with no directional bias to light. Syn OS-B′ was slightly less motile but exhibited positive phototaxis. This binary consortium displayed cooperative behavior by moving further than either species alone and formed ordered arrays where both species aligned with the light source. No cooperative motility was observed when a nonmotile pilB mutant of Syn OS-B′ was used instead of Syn OS-B′. The binary consortium also produced more adherent biofilm than individual species, consistent with the close interspecies association revealed by electron microscopy. We propose that cyanobacteria and Chloroflexota cooperate in forming natural microbial mats by colonizing new niches and building robust biofilms.